Influence of Internet plus on cyberspace security and the technology development trend in Internet plus era - De-yu YUAN; Xiao-juan WANG; Jian-chao WAN (网络与信息安全学报)
The rapid development of network and information technology have profoundly changed the way of human life,work and thinking.However,in sharp contrast to technological development and subscriber growth,the global cyberspace security situation is becoming increasingly complex.Therefore,the importance of cyberspace security should be emphasized,and building safe and stable cyberspace is of great significance in the Internet plus era.The fact that the scale of the network continues to expand,the application model becomes more and more innovative,and the application environment becomes more and more complex brings a lot of new security issues.Based on this consideration,the influence of Internet plus on cyberspace security and the technology development trend was analyzed,and the countermeasures and suggestions were given.